High-throughput development of highly active catalyst system to convert bioethanol to 1, 3-butadiene. Issue 8 (13th July 2021) - Shinke, Yu; Miyazawa, Tomohisa; Hiza, Misao; Nakamura, Isao; Fujitani, Tadahiro
Abstract : The development of highly active catalysts for the conversion of ethanol to 1, 3-butadiene using high-throughput catalyst preparation and evaluation systems. Abstract : Herein, we describe the development of highly active catalysts for the conversion of ethanol to 1, 3-butadiene using high-throughput catalyst preparation and evaluation systems. Assuming a two-stage reactor for converting ethanol to acetaldehyde and ethanol/acetaldehyde to 1, 3-butadiene, we conducted rapid screening for the optimal catalyst for each reaction. We found that using Ag/SiO2 and HfO2 /SiO2 as catalysts in the first- and second-stage reactors, respectively, resulted in high 1, 3-butadiene productivity (99% ethanol conversion and 63% 1, 3-butadiene selectivity).